The Dynamic Changes of White Blood Cell Count and Lymphocyte Count and Compare their Levels in the Early Stage of Covid-19 - Ling Wang (International Journal of Coronaviruses, 2021)
COVID-19 is a new infectious disease, which needs to explore the clinical value of white blood cell count and lymphocyte to provide help for diagnosis and treatment.COVID-19 cases were Selected that admitted to 2 hospitals in Guizhou, China. WBC and LYM in the 1st day, in the 4th day and in the 7th day after onset were collected. There were not any differences in The WBC and LYM in the 4th day and the 7th day between the two groups.WBC and LYM in the 1st day in the moderate group were lesser than in the mild group. WBC and LYM were no dynamic changes in the mild group. In moderate group, WBC and LYM in the 1st day were lesser than in the 4th day. The levels in the 4th day and the 7th day were no differences. The conclusion was In the early stage of COVID-19, the WBC and LYM in moderate patients were significantly decreased within 4 days after onset, and could be restored to normal level after 4-7 days. However, no dynamic changes were observed in mild patients within 7 days.
Keywords: COVID-19